2008
DOI: 10.1590/s0103-50532008000700003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ferrocenyl oxindole compounds with potential anticancer activity

Abstract: Compostos oxindol-ferrocenos com potencial atividade anticâncer foram preparados a partir de reações de oxindóis substituídos e carboxaldeído-ferroceno na presença de KOH como catalisador. Os produtos foram caracterizados por dados espectroscópicos incluindo RMN de 1 H e 13 C, infravermelho e espectrometria de massas. As configurações E e Z foram estabelecidas por experimentos de nOe ou NOESY.A series of ferrocenyl oxindoles with potential anticancer activity were prepared from the reactions of substituted oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 8 publications
(13 reference statements)
1
9
0
Order By: Relevance
“…Of interest, three of a set of seven substituted 3-methylideneindolin-2-ones (Spencer et al, 2010) and one of the two isomeric ferrocenyl oxindoles (Spencer et al, 2009) previously reported by us also have Z 0 > 1. The geometry of both crystallographically independent ferrocene species in (IV) are comparable with the ferrocenyl oxindoles and substituted oxindoles previously reported by us and others (Silva et al, 2008;Spencer et al, 2009Spencer et al, , 2010 and with fragments found in a search of the Cambridge Structural Database (CSD, Version 5.32; Allen, 2002). All four oxindole units in (IV) exist as the (E)-isomers, with the average of the four bond angles C11/C111-C12/C112-C13/C113 and C20/C120-C21/C121-C22/C122 being 118.8 (5) .…”
Section: Commentsupporting
confidence: 82%
See 1 more Smart Citation
“…Of interest, three of a set of seven substituted 3-methylideneindolin-2-ones (Spencer et al, 2010) and one of the two isomeric ferrocenyl oxindoles (Spencer et al, 2009) previously reported by us also have Z 0 > 1. The geometry of both crystallographically independent ferrocene species in (IV) are comparable with the ferrocenyl oxindoles and substituted oxindoles previously reported by us and others (Silva et al, 2008;Spencer et al, 2009Spencer et al, , 2010 and with fragments found in a search of the Cambridge Structural Database (CSD, Version 5.32; Allen, 2002). All four oxindole units in (IV) exist as the (E)-isomers, with the average of the four bond angles C11/C111-C12/C112-C13/C113 and C20/C120-C21/C121-C22/C122 being 118.8 (5) .…”
Section: Commentsupporting
confidence: 82%
“…We and others have recently published the synthesis of the isomeric ferrocenyl oxindoles, (E)-and (Z)-3-(ferrocenylmethylidene)indolin-2-one, denoted (E)and (Z)-(III), which are readily separated and have excellent anticancer properties (see scheme). We have shown that (E)and (Z)-(III) display intermolecular NHÁ Á ÁO C hydrogen bonding in the solid state (Silva et al, 2008;Spencer et al, 2009).…”
Section: Commentmentioning
confidence: 91%
“…As a result, ferrocene was incorporated into a large number of molecules such as water soluble polymers [61][62][63][64], DNA intercalator [65], phosphino compounds [66][67][68][69], and other biomolecules [70][71][72][73]. Diferrocenyl compounds [74] and a variety of other small ferrocenyl molecules [75][76][77][78][79] have also been investigated for anticancer activity.…”
Section: Anticancer Ferrocenesmentioning
confidence: 99%
“…Among metallocenes there are compounds with antiproliferative effect, antibiotics, and inhibitors of enzymes. [6][7][8][9] Conjugates of ferrocene with well-known drugs were reported. [10][11] Ferrocene-containing compounds often possess unexpected biological activity.…”
Section: -2mentioning
confidence: 99%